Abnormal Somatosensory Behaviors Associated With a Gain-of-Function Mutation in TRPV3 Channels - Fatima, Mahar; Slade, Hannah; Horwitz, Lorraine; Shi, Angela; Liu, Jingyi; McKinstry, Delaney; Villani, Troy; Xu, Haoxing; Duan, Bo (Frontiers in Molecular Neuroscience, 2022)
Thermosensitive transient receptor potential V3 (TRPV3) is a polymodal receptor implicated in nociceptive, thermoceptive, pruritoceptive, and inflammatory pathways. Reports focused on understanding the role of TRPV3 in thermoception, or nociception are not conclusive. Previous studies also show that aberrant hyperactivity of TRPV3 channels results in spontaneous itch and dermatitis-like symptoms, but the resultant behavior is highly dependent on the background of the animal and the skin microbiome. To determine the function of hyperactive TRPV3 channels in somatosensory sensations, we tested different somatosensory behaviors using a genetic mice model that carries a gain-of-function point mutation G573S in the Trpv3 gene (Trpv3G573S). Here we report that Trpv3G573S mutants show reduced perception of cold, acetone-induced cooling, punctate, and sharp mechanical pain. By contrast, locomotion, noxious heat, touch, and mechanical itch are unaffected in Trpv3G573S mice. We fail to observe any spontaneous itch responses and/or dermatitis in Trpv3G573S mutants under specific pathogen (Staphylococcus aureus)-free conditions. However, we find that the scratching events in response to various pruritogens are dramatically decreased in Trpv3G573S mice in comparison to wild-type littermates. Interestingly, we observe sensory hypoinnervation of the epidermis in Trpv3G573S mutants, which might contribute to the deficits in acute mechanical pain, cool, cold, and itch sensations.